2017
DOI: 10.1021/acs.joc.6b02755
|View full text |Cite
|
Sign up to set email alerts
|

Substituent and Solvent Effects on the Stability of N-Heterocyclic Carbene Complexes with CO2

Abstract: Carbon dioxide forms covalent complexes with N-heterocyclic carbenes. These complexes are of interest in catalysis as well as for their potential use in various carbon capture and storage strategies. A previous report showed that the stability of one such complex, N,N-dimethylimidazolium 2-carboxylate, was remarkably sensitive to solvent polarity. Polar environments lead to a kinetically stronger, shorter, and more polar bond between the carbene and CO. The current study shows that this solvent effect is gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 37 publications
1
26
1
Order By: Relevance
“…A few isolated systems (carbenes, guanidines and more recently phosphines) or combined in the form of frustrated Lewis pairs have been described to be able to react with CO 2 and form covalent aggregates . The mechanism and environment effect of the sequestration and activation of CO 2 has been studied theoretically by different groups …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A few isolated systems (carbenes, guanidines and more recently phosphines) or combined in the form of frustrated Lewis pairs have been described to be able to react with CO 2 and form covalent aggregates . The mechanism and environment effect of the sequestration and activation of CO 2 has been studied theoretically by different groups …”
Section: Introductionmentioning
confidence: 99%
“…[11,12] The mechanism and environment effect of the sequestration and activation of CO 2 has been studied theoretically by different groups. [13][14][15][16][17][18][19][20] Phosphatrane molecules are a tricyclic cage-like heterocycles which present the possibility to have a transannular dative bond with a nitrogen or another heteroatom. The pioneer synthetic work in the groups of Alder and Verkade [21][22][23][24][25][26][27][28][29] showed that depending of the size, substituents and environment they can adopt out:out and/or in:out conformations.…”
Section: Introductionmentioning
confidence: 99%
“…modeled the reaction of dimethyl imidazole carbene with CO 2 in the presence of a methanol molecule . Two recent articles by Denning and Falvey have explored theoretically the effect of both solvent and substitution patterns on the energy profile of the NHC–CO 2 decarboxylation reaction . The results of these studies indicated the importance of the polarity of the solvent in the stabilization of the NHC–CO 2 molecule, the lability of the C−C bond due to the substituents around the CO 2 group, and the electronic effect on the distant carbon atoms of the NHC molecules.…”
Section: Introductionmentioning
confidence: 99%
“…For example, 1-n-butyl-3methylimidazolium diacyanimide[ BMIm.N(CN) 2 ]I Lp hoto-reduces CO 2 to produce 110 mmol g À1 of CO (the ESR signal is still observable despite the low intensity,a ss hown in Figure S11b); whereas, in 1-n-butyl-3-methylimidazolium hexafluorophosphate (BMIm.PF 6 )I Ln op roduction of CO was detected.T his phenomenon may be correlated with the basicity of the anions, which may play an important role in the CO 2 sorption, and subsequentf ormationo ft he BMIm.CO 2 zwitterion that drives the generation of CO during the photoreduction process. Therefore, the most probable limiting step is the formation of imidazolium-CO 2 adduct, [26] which is related to anion basicity.…”
Section: Resultsmentioning
confidence: 99%